Reconfigurable monopole antenna for WLAN/WIMAX applications - Iddi, H. U. (2013)
In this paper, a simple reconﬁgurable monopole antenna for WLAN/WiMAX application is presented. The proposed antenna has been designed and compared to a three patch strips triple band monopole antenna which operate at 2.45GHz, 3.5GHz and 5.8GHz frequency bands. The antenna has been simulated using CST software studio and fabricated on FR4 substrate. The proposed antenna provides triple bands in which the bandwidth of 367MHz for 2.45GHz, 799MHz for 3.5GHz and a bandwidth of 3.47GHz for 5.8GHz has been obtained. The results show that the measured and simulated return loss characteristic of the optimized antenna satisﬁes the requirement of the 2.4/5.8GHz WLAN and 3.5GHz WiMAX antenna application. The proposed reconﬁgurable antenna is low proﬁle, compact and small in size and show good performance for WLAN/WiMAX bands. There is good agreement between the measurement and simulation results in terms of return loss and radiation pattern.